The Sprouting Consciousness of the Psychologically Oppressed Wife in “The Steel Brassiere” by Iris Sheila G. Crisostomo - Asmarani, Ratna (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
The purpose of this paper is to analyze Crisostomo’s short story entitled “The Steel Brassiere” to find out how the personal consciousness of the female protagonist emerges, the trigger of the emergence, and the psychological oppressions that she experiences as a domestic wife of a patriarchal husband. The concepts used to support the analysis are three modes of being of existentialism, existential psychology, patriarchy, husband, the personal is political, bras as cultural myth and in the perspective of feminism, and types of verbal abuse. The analysis applies the feminist literary criticism, considering that the focus of analysis is a woman, and the contextual method of literary research which combines intrinsic and extrinsic elements. The analysis is done in a qualitative way supported by library research with its close reading strategy. The result shows that once the obedient wife who keeps her psychological distress by herself is triggered by the steel bra which gives the hint of the image of a strong independent female, her personal consciousness emerges inextinguishable. She is ready to change into a woman who is prepared to refuse the husband’s abrupt order that she is not willing to do and is calmly waiting for the consequences.